Secondary impacts of constipation in acute lymphoblastic leukemia in U.S. children's hospitals. Issue 11 (7th September 2021) - Belsky, Jennifer A.; Batra, Sandeep; Stanek, Joseph R.; O'Brien, Sarah H.
Abstract: Background: Childrenwith acute lymphoblastic leukemia (ALL) suffer a litany of chemotherapy‐induced side effects. Constipation secondary to vinca alkaloids, psychological stressors, and opioid use are common issues for children newly diagnosed with leukemia. This study investigated the morbidity associated with constipation including infections, mucositis, and healthcare utilization in hospitalized children with ALL receiving induction chemotherapy. Methods: We analyzed data from 48 children's hospitals in the Pediatric Health Information System, extracting patients 1–21 years of age with ALL, hospitalized for induction from October 2015 through December 2019. Data were analyzed using nonparametric statistics, and comparisons of outcomes between those with and without constipation were presented as adjusted odds ratios (aOR). Results: We identified 2586 (56%) patients with constipation out of a total of 4622 unique ALL patients in induction. Compared to patients without constipation during induction, patients with constipation were significantly more likely to have mucositis (aOR = 2.30; p = 0.0010), perirectal issues (aOR = 3.21; p = 0.0092), or abdominal radiograph exposure (aOR = 2.40; p < 0.0001). The median length of induction hospitalization was significantly greater in those with constipation compared to those without constipation (10 days vs. 8 days; p < 0.0001). Conclusions: Children with ALL suffering from constipation during induction therapy have increased length of stay, mucositis, imaging, and overall healthcare utilization compared to children without constipation. Further research should explore the causative relationship between constipation and infections. Increased attention should be given to constipation management in patients with ALL at the start of induction therapy, particularly in patients with complications or prolonged hospitalizations.